How to feed a child with cystic fibrosis - Yu. S. Pinegina (Лечащий Врач, 2021)
The article is devoted to various aspects of nutritional support for children with cystic fibrosis. The basic principles of nutrition of such patients are considered. The article presents the results of a retrospective observational clinical study of the use of a specialized product for therapeutic nutrition, in which the effect of the use of a specialized food product on physical development, the course of the disease and the quality of life of children with cystic fibrosis was studied. The patients included in the study had a diagnosis of cystic fibrosis, documented according to the 2014 European Consensus. The age of the children included in the study ranged from 2 to 17 years. The analysis of indicators of physical development, data on the history of development and diseases of children: the frequency of exacerbations of chronic bronchopulmonary process during the study period, the need for intensive therapy, the presence of complications. The level of physical development in patients was assessed by the body mass index (BMI). Children who received additional food for a long time as part of the daily diet had the best indicators of physical development, which was expressed in high BMI values. Statistically significant indicators were obtained when comparing the group of children who received food regularly for three years, and the control group. The lower frequency of exacerbations requiring hospitalizations also indirectly indicates the advantage of patients in the study groups over the control.